Oinoanda, Türkei: Die Arbeiten der Jahre 2014 und 2015 - Bachmann, Martin (e-Forschungsberichte des DAI, 2023)
After the last field campaign in Oinoanda in 2012, the research program continued with an architectural-epigraphic survey focused on the monumental inscription of Diogenes of Oinoanda and its urban context. The relation between inscription and public space to be examined here as a case study is an issue crucial to questions of ancient media placement in general. To fill some gaps in the 3D documentation of the inscription a Museum campaign was prepared in 2014 and carried out in 2015 in order to scan the blocks in the depot house of Oinoanda. Furthermore, new 3D images of the site were produced with a drone.